Web Design and Development of 'Peduli PMI' System for Managing Complaints and Protection of Indonesian Migrant Workers - Dwiyaniti, Murie; Wardhani, Rika Novita; Nadhiroh, Nuha; Wulandari, Asri; Frendiana, Viving; Biyanto, Farhan Yuswa (Universitas Multimedia Nusantara, 2025)
Indonesian Migrant Workers (PMI) face high occupational risks, making it essential to provide them with appropriate attention to prevent and reduce unwanted incidents. A computerized system in the form of a web application can assist administrators in managing PMI complaints and protection more effectively. Through this system, administrators can handle PMI data, manage content such as news and announcements, monitor statistics related to users, complaints, and protection cases, and manage complaint and protection data submitted by PMI to ensure their safety. This study aims to design and develop a Complaint and Protection Management System Website for PMI in Malaysia. The system includes four main features: secure admin access with login, user registration, password recovery, and administrative capabilities. Administrators can manage user data, handle complaints, update report status, respond to complaints, view other administrators' lists, and modify personal data and password settings. Additionally, they can manage front-end content for the mobile application, including news and announcements. This system is designed to be efficient and responsive to the needs of PMI. The study conducted four tests”Functionality Testing, API Testing, Performance Testing, and Security Testing. Results indicate that the system meets required standards, with no errors detected during testing.